THE COMPARISON BETWEEN ERROR-LESS LEARNING AND ERRORFUL LEARNING IN VIRTUAL REALITY ON POKÉMON THEME - Ma, Yuan; Wang, Qisen; Fujinami, Tsutomu (MATTER: International Journal of Science and Technology, 2020)
We discuss the feasibility of cognitive training in the virtual reality (VR) environment by comparing both error-less (EL) and errorful (EF) ways with Pokémon characters as training material. We developed a VR environment for experiencing the procedural and a questionnaire for collecting data. We tested the performance of this application as a preliminary study and received the feedbacks from participants, who are young student. We found firstly that they could be engaged in the cognitive training with Pokémon theme. Secondly, they showed a better training effect under EL condition although they found the training under EF condition more fun than that under EL condition. Thirdly, participants were fond of the VR device as a presenting way. We plan to carry out another experiment with a modified version to collect feedbacks from the healthy elderly. Accordingly, we believe that the proposed approach is acceptable in practice. From this perspective, we expect that our work can benefit the elderly by attracting them to take part in such EL-based exercises.